Development of an Open-ended Numeracy Literacy Instrument: Context of Timorese Culture - Meiva Marthaulina Lestari Siahaan; Cecilia Novianti Salsinha; Hendrika Bete; Lailin Hijriani (AlphaMath : Journal of Mathematics Education, 2026)
Addressing complex problems requires multiple and sustainable solution strategies, highlighting the importance of students’ numeracy literacy. However, existing assessment practices often fail to capture students’ higher-order thinking and problem-solving flexibility, particularly in algebraic contexts. An open-ended, locally wisdom–based instrument is considered appropriate for fostering students’ problem-solving abilities; however, it is rarely implemented in regular classroom instruction. Furthermore, research on the development of open-ended numeracy literacy instruments within Timorese culture remains limited. This study aims to develop and validate an open-ended numeracy literacy instrument in the algebra domain to address this gap. The study employed a design-based development approach using Tessmer’s formative evaluation, which includes preliminary study, expert review, one-to-one, small-group, and field-test stages. Qualitative data were obtained from expert validation, student feedback, and interviews, while quantitative data were collected through student response questionnaires and test results. The findings reveal that the developed instrument meets the criteria of validity, practicality, and reliability. Furthermore, the instrument demonstrates moderate difficulty and acceptable discrimination, indicating its effectiveness in distinguishing students’ abilities. This study contributes a valid and reliable open-ended assessment tool that can support the enhancement of students’ numeracy literacy and promote meaningful mathematics learning in algebra.